Experimental study for the production of calcium manganate particles and their use in chemical-looping combustion - Abukar, Abubakar; Andersson, Moa; Humpage, Samuel; Jonsson, Andreas; Lieback, Milly; Moilanen, Erik (My University, 2022)
With higher demands for energy comes higher demands on current combustion processes, more specifically the demand to reduce the emission of CO2. One solution is the chemical-looping combustion process (CLC) using oxygen carriers to isolate CO2 in pure form. Thereafter carbon capture and storage (CCS) is applied, where the CO2 is captured and stored deep in the ground or under the bottom of the sea. In this report the focus was to find a method to produce the oxygen carrier calcium manganate, CaMnO3−δ, in a way that results in cheap and strong oxygen carriers with chemical looping with oxygen uncoupling (CLOU) properties. To be able to implement CaMnO3−δ as a competitive oxygen carrier it should be produced by manganese ore, since it could get to expensive with pure manganese. To find the best production method and the properties of the oxygen carriers, they were subjected to a series of laboratory tests. A method was chosen and multiple samples were produced using different combinations of temperature and manganese ore. The samples’ physical attributes were tested and ranked. The three best samples were chosen and tested in a fluidized bed batch reactor to see how they could potentially react in a CLC system. In the reactor the oxygen carriers exhibited CLOU properties as was seen from the release of of oxygen to the gas phase. The samples showed an ability to release ∼ 2 wt% oxygen while approximately 10 % of that oxygen was release through oxygen uncoupling. The attrition test showed that the most reactive particles all had the highest degree of attrition, particles produced from Eramet ore sintered at 1265 °C, was shown to have an attrition rate of 1.35wt% h from a jet cup attrition test . An X-ray diffractometer verified that calcium manganate particles were present in all three samples. A techno-economic analysis of the production of oxygen carrier estimated a required concurrent mass in a 1 MW CLC system of 41 kg for the sample with the lowest cost. For the same sample a CLC system would additionally require a flow 8786 kg/year of fresh oxygen carriers due to the measured attrition rate. These results corresponds to a yearly cost of 1015066 SEK/year for the required materials and the production of the best sample in large scale. The main expense of was the cost of heating, calcining the limestone as well as sintering, as the yearly cost of the ovens is responsible for 87 % of the yearly cost. As discussed in this report, the best way to improve the results of the particles and lower the cost would be to research the lifetime by testing it in a real CLC environment and also continuing to further improve it. A suggestion for a way to approach this is to research the sintering process as this is tightly connected to lifetime.